1985
DOI: 10.1007/bf01256474
|View full text |Cite
|
Sign up to set email alerts
|

Daily and seasonal rhythmicity in the methylation of pineal indolic compounds in adult male golden hamsters, kept under natural conditions

Abstract: Seasonal rhythmicity in the reproductive cycle was demonstrated in golden hamsters exposed to natural conditions. Testes regress in weight and function from October up to April. Reproductive functional testes are found in June. Although less marked, body weight also shows seasonal variations: a retarded growth in winter and early spring. In the pineal gland of these animals diurnal and seasonal rhythmicity was found in the synthesis of various MI. It has been concluded that rhythms in the pineal of animals kep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Moreover, because of technical problems the dissections at week 0, 5 and 9 were carried out at noon which is not the most optimal timepoint for MI synthesis according the literature. However, since the potency of the pineal to synthesize MI is measured and since in earlier experiments (Van Benthem et al, 1985) it was shown that also during daytime the pineal possesses this potency, the data obtained at noon are presented and discussed. For comparison in Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, because of technical problems the dissections at week 0, 5 and 9 were carried out at noon which is not the most optimal timepoint for MI synthesis according the literature. However, since the potency of the pineal to synthesize MI is measured and since in earlier experiments (Van Benthem et al, 1985) it was shown that also during daytime the pineal possesses this potency, the data obtained at noon are presented and discussed. For comparison in Fig.…”
Section: Discussionmentioning
confidence: 96%
“…The heavy arrows indicate a stimulating and the interrupted heavy arrows a putative stimulating effect. The interrupted thinner arrow points to a putative blockade on that specific metabolic reaction production of aMT (Van Benthem et al, 1985) although both compounds are considered pineal antigonadotropic compounds. The changes in MI synthesis which occurred during early recrudescence, pointing to a regulating function of several of these compounds, are not in agreement with the literature.…”
Section: Discussionmentioning
confidence: 98%